1997
DOI: 10.1021/ja973199x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Aspects of the Alternating Copolymerization of Propene with Carbon Monoxide Catalyzed by Pd(II) Complexes of Unsymmetrical Phosphine−Phosphite Ligands

Abstract: The reaction steps responsible for the highly enantioselective asymmetric copolymerization of propene with carbon monoxide catalyzed by a cationic Pd(II) complex bearing an unsymmetrical chiral bidentate phosphine−phosphite, (R,S)-BINAPHOS [(R,S)-2-(diphenylphosphino)-1,1‘-binaphthalen-2‘-yl 1,1‘-binaphthalene-2,2‘-diyl phosphite = L1], have been studied. Stepwise identification and characterization were carried out for catalyst precursors (SP-4-2)- and (SP-4-3)-Pd(CH3)Cl(L1) (1a and 1b) and (SP-4-3)-[Pd(CH3)(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
178
0
5

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 195 publications
(197 citation statements)
references
References 50 publications
14
178
0
5
Order By: Relevance
“…66 In the case of CO/alkene copolymerization the site selective coordination of the alkene was observed for both palladium complexes with amine-imine ligands, 27 with hybrid P-N ligands 48 and with the phosphino-phosphite (P-PO) molecule BINAPHOS. 67 A mechanistic hypothesis involving cis/trans isomerization was invoked.…”
Section: Reactivity Studiesmentioning
confidence: 99%
“…66 In the case of CO/alkene copolymerization the site selective coordination of the alkene was observed for both palladium complexes with amine-imine ligands, 27 with hybrid P-N ligands 48 and with the phosphino-phosphite (P-PO) molecule BINAPHOS. 67 A mechanistic hypothesis involving cis/trans isomerization was invoked.…”
Section: Reactivity Studiesmentioning
confidence: 99%
“…4(b)]. 26,43 Jiang and Sen 25 reported that poly(propene-alt-carbon monoxide) made with an enantiomerically pure catalyst showed a single 13 C NMR peak for the carbonyl carbon in the presence of a chiral europium shift reagent and that poly(propenealt-carbon monoxide) made from a racemic mixture of the catalyst showed two carbonyl peaks. Because the polycarbonate poly(cyclohexene oxide-altcarbon monoxide) can be hydrolyzed into trans-1,2-diol and CO 2 under basic aqueous conditions under reflux, the degree of asymmetric induction, 80% ee, could be deter- mined unambiguously by chiral gas chromatography analysis of the isolated trans-cyclohexane-1,2-diol.…”
Section: Highlightmentioning
confidence: 99%
“…8 Potassium tert-butoxide (0.19 g, 1.7 mmol) was added to the solution of CH 3 PPh 3 I (0.35 g, 0.86 mmol) in THF (15 mL) at 0 • C. A solution of the polyketone 1 (0.030 g, 0.43 mmol) in CH 2 Cl 2 (1.8 mL) was added to the mixture at the same temperature, and the resulting mixture was stirred for 20 h at room temperature. The reaction mixture was filtered through a Celite pad and the filter cake was washed with chloroform (100 mL) but no polymeric material was extracted.…”
Section: Wittig Reaction Of Isotactic Poly(co-alt-propene) (1)mentioning
confidence: 99%
“…These are γ-polyketones which have an asymmetric carbon at the α-position of each carbonyl group. [8][9][10][11] The carbonyl groups can be transformed into various functional groups, and therefore chemical modification of the carbonyl groups would provide new classes of chiral polymers. 9,12 Although many examples were reported for the functionalization of polyketones, mainly poly(ethene-co-CO) or achiral poly(propene-alt-CO), no report has ever appeared for the nucleophilic addition of carbanions to the carbonyl groups.…”
Section: Introductionmentioning
confidence: 99%